Simultaneous removal of arsenate and nitrate from aqueous solutions using micellar-enhanced ultrafiltration process - Bahmani, Pegah; Maleki, Afshin; Rezaee, Reza; Khamforoush, Mehrdad; Yetilmezsoy, Kaan; Athar, Saeed Dehestani; Gharibi, Fardin (ELSEVIER, 2019)
Arsenate (As(V)) and nitrate (NO3- removal from aqueous solutions was investigated via micellar-enhanced ultrafiltration (MEUF) using a prepared polyacrylonitrile (PAN) membrane and cetylpyridinium chloride (CPC) as the cationic surfactant. The PAN ultrafiltration (UF) membrane was produced using the phase inversion method and used in a dead-end cell system. The morphology and physiochemical properties of the prepared membrane were characterized using SEM, EDX, XRD, FTIR, and AFM. Parameters, including surfactant concentration, solution pH, and transmembrane pressure (TMP) were examined to determine their effects on the permeate flux and removal efficiency of As(V) and NO3-, besides CPC rejection. Increasing CPC concentration from 0.1 to 5 mM, removal of As(V) and NO3- increased from 49.3% to 96.9% and from 0.3% to 90.5%, and the permeate flux reduced from 36.6 to 10.2L/m(2)/h and from 54.2 to 33.3 L/m(2)/h, respectively. In addition, simultaneous removal of As(V) and NO3- via MEUF was studied, which showed that removal of NO3- was majorly prevented by As(V) because of competitive binding of CPC micelles between NO3- and As(V); however, As(V) removal was only slightly inhibited by NO3-. It was shown that the prepared PAN membrane could remove more than 90% of As(V) and NO3- under optimal conditions (CPC concentration = 5 mM, pH = 7-8, and TMP = 1 bar), using the MEUF process.
Keywords: Arsenate; Nitrate; Micellar-enhanced ultrafiltration; Ultrafiltration; Membrane; WASTE-WATER; OPERATING-CONDITIONS; ADSORPTIVE REMOVAL; ANIONIC METALS; GROUNDWATER; SEPARATION; OXIDATION; PHENOL; MEUF; Engineering; Water Resources